A Study of Mn(II) Ion Capture by Mesoporous Silica - Na-Juan Yuan; Tie-Zhen Ren; Jeppe Christensen (Adsorption Science & Technology)
The removal of Mn(II) ions from water using mesoporous silica as the adsorbent material is discussed. The mesoporous silica was prepared in an economic manner through the use of sodium silicate as an inexpensive source of silica and decaoxyethylene cetyl ether [C 16 (EO) 10 ] as the template agent. The properties of the material were characterized and its adsorption capacity for Mn(II) ions from aqueous solution investigated by varying parameters such as the pH of the initial suspension, the contact time, the initial concentration of Mn(II) ions in the solution and the adsorbent dosage. With no subsequent modification, the prepared materials exhibited a high adsorption capability towards Mn(II) ions with q e = 44 mg/g. The adsorption isotherms could be described by both the Langmuir and Freundlich models, the former model providing a better representation of the adsorption process. Characterization using UV–vis spectroscopy, nitrogen sorption isotherms and thermogravimetric analysis after adsorption indicated that the Mn(II) ions were adsorbed onto the mesoporous silica surface.